Methods for Calculation of Undelivered Electricity in a Medium Voltage Network that is not Integrated into the Remote Control System - Vrcelj, Nada S (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
The method is based on data obtained from the so-called hand-held measuring current at the 10 kV voltage level and from reports of outages at reclosers that are installed in a part of a network that is observed. First, it calculates the electrical load of the main distribution power lines, and then simulates the corresponding power flow and calculates the undelivered electricity. The method was applied to parts of the network PD ED Belgrade that are not in the remote control system and is developed for the purpose of considering the effects of automation in the 10 kV PD ED Belgrade